Spring diet and feeding strategy of the European sprat Sprattus sprattus (L., 1758) from the Black Sea coast of Turkey - Bahar Bayhan (Turkish Journal of Agriculture: Food Science and Technology, 2015)
This study aims to identify the spring diet composition and feeding strategy of the European sprat, Sprattus sprattus. Diet composition of European sprat was investigated for the first time in the central Black Sea coast of Turkey. Examined of the 115 specimens (6 - 9.1 cm total length) of stomach, 12 (10.4%) had emty. Diet analysis was described based on gravimetric percentages (W%), frequency of abundance (N%), frequency of occurrence (%F) and relative importance index (IRI%). Feeding strategy was analyzed and graphically (Costello) represented, considering the frequency of abundance (N%) and frequency of occurrence (%F) indexes and grouping prey into higher taxonomic categories. Twenty species were identified, belonging to four prey groups: Polychaeta, Crustacea, Mollusca and Chaetognatha. Finally copepods proved to be the most important food item considering the above-cited indexes. All other prey taxa were identified as accidental preys. At least seven copepod species were identified, where Calanus euxinus appeared all round with %IRI≥50. Also results of feeding strategy analyses revealed a trophic specialization toward a single prey.